Low work function, long lifetime filament for electron beam-based, wire-fed metal additive manufacturing - Nguyen, Bao Gia, author; Bradley, Thomas, advisor; Williams, John, advisor; de la Venta Granda, Jose, committee member (Colorado State University. Libraries, 2018)
Tantalum filaments are used in electron beam additive manufacturing to thermionically emit electrons that are used to build near-net shape, metal parts. High operating temperatures are required to emit electrons which consequently limits the lifetime of these filaments. This thesis presents the thermionic emission characteristics of drop-in filament replacements that incorporate barium calcium aluminate cermets. Barium calcium aluminate is a low work function material used with hollow cathodes in electric propulsion devices to provide very long service lifetimes by acting as a moderate temperature, electron source. A marriage of these two technologies may limit downtime and increase the productivity and output of electron beam additive manufacturing. Results of extended runtime tests are presented from configurations that immerse the modified filament in plasma and operate it as a vacuum emitter. The effect of contamination by air and fabrication methods are examined and evaluated based on effective work function and current density measurements. The latter includes formation methods for barium diffusion orifices as well as surface preparation methods for cermets. The experimental data collected were used to validate a predictive model that evaluates emission current densities, in both temperature and space-charge limited conditions, and effective work functions based on the fractional surface coverage of barium over a tantalum substrate.
Keywords: additive manufacturing; low work function; electron beam; 3D printing